Cataract surgery complications as a cause of visual impairment in a population aged 50 and over Complicações de facectomias como causa de baixa visual em uma população com 50 ou mais anos de idade - Denise Fornazari de Oliveira; Rodrigo Pessoa Cavalcanti Lira; Álvaro Pedroso Carvalho Lupinacci; Marcelo Paccola; Carlos Eduardo Leite Arieta (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
The purpose of this study was to measure the extent to which complications relating to cataract surgery are a cause of visual impairment in a population aged 50 and over from the city of Campinas, São Paulo State, Brazil. An assessment of cataract surgery services was conducted using random cluster sampling, with the sample composed of 60 clusters of 40 people aged 50 years or older. Of the selected sample of 2,400 subjects, 92.67% were examined. Of these 2,224 examined subjects, 75 (3.37%) presented bilateral visual impairment and 164 unilateral, while a total of 314 (7.06%) eyes presented visual impairment. 352 eyes had undergone cataract surgery. The causes of visual impairment after surgery were concurrent eye disease (56%), surgical complications (28.8%) and refractive errors (15.2%). Cataract surgery complications represented the 5th most important cause of visual impairment. The other main causes were cataract, posterior segment disorders, diabetic retinopathy and glaucoma. These results suggest cataract surgery complications are a major cause of visual impairment in this population. Their prevention and treatment must be part of public health care policies. Objetivou-se avaliar a relevância das complicações de facectomias como causa de baixa acuidade visual na população > 50 anos em Campinas, São Paulo, Brasil. Uma avaliação dos serviços de cirurgia de catarata foi conduzida utilizando amostragem aleatória de agrupamentos populacionais, sendo composta por 60 agrupamentos de 40 pessoas > 50 anos. Na amostra de 2.400 indivíduos, 92,67% foram examinados. Dos 2.224 examinados, 75 (3,37%) apresentaram baixa acuidade visual bilateral, 164, unilateral. e um total de 314 (7,06%) olhos apresentou baixa acuidade visual. Trezentos e cinqüenta e dois olhos tinham sido submetidos a facectomias. As causas de baixa acuidade visual pós-cirurgia foram doenças oculares concomitantes (56%), complicações cirúrgicas (28,8%) e erros refrativos (15,2%). Complicações de cirurgias de catarata foram a quinta causa mais importante de baixa acuidade visual. Outras causas principais foram catarata, doenças oculares do segmento posterior, retinopatia diabética e glaucoma. Estes resultados sugerem que complicações de cirurgias de catarata é uma importante causa de baixa acuidade visual na população em estudo. Sua prevenção e tratamento precisam fazer parte das políticas de saúde pública.